Makna Ruang Publik Bagi Pedagang Kaki Lima: Studi tentang Resistensi terhadap Penggusuran (Proceeding SENDI_U, 2015)
This paper is going to solve the fundamental problem, namely (1) why the government is doing demolition oreviction of the street vendors Kokrosono and Basudewo, and (2) why public space is important for vendors.This study is a qualitative study, the data were taken with the interview, observation, and literature. Datawere analyzed with interactive qualitative analysis techniques. The results show, that the Semarang citygovernment to curb or eviction of the street vendors Kokrosono and Basudewo based on (1) the provision oflocal regulations and other regulatory requirements, (2) to create a public space that is orderly, clean, safe,and convenient for all city dwellers. Public spaces or locations for street vendors selling a strategic placethat must be maintained from the other party intervention. This is due to (1) vendors do not have a permanentto run a business, (2) selection of the location on the road, because it gives an attraction for buyers and usersof services.Keyword: eviction, public spaces, resistance, street vendors